The characteristics of people with mental illness who are under treatment in traditional healer centres in Sudan - Sorketti, E.A.; Zuraida, N.Z.; Habil, M.H. (SAGE Publications, 2012)
Aims: To determine the general characteristics of people with mental disorders in traditional healers centres in Sudan in terms of sociodemographic profile, common clinical presentations and diagnostic features, and to look at the treatment methods and intervention procedures used in these centres for treating people with mental illness. Methods: This is a descriptive cross-sectional study using both quantitative and qualitative research methods. All inpatients with mental illness (405) from 10 selected traditional healers centres in Sudan who gave consent were interviewed, using a specially designed questionnaire and the Mini International Neuropsychiatric Interview (MINI). Results: Most of the visitors to the centres were from central Sudan with a mean age of 31 years, illiterate or with only a primary basic education, male and jobless. The average mean duration of stay in the traditional healer centre was five months and the mean duration of untreated illness before coming to the centre was 13 months. Only 17% reported a history of alcohol abuse and only 11% of drug abuse. The most common prevalent diagnosis was psychotic disorder. Conclusion: This study improves the understanding about what types of people with mental illness are treated at these traditional healer centres and gives recommendations that can help in improving the quality of services in these centres. It can probably be used in building bridges of collaboration between these centres and the available mental health and psychiatric services in Sudan, especially at primary healthcare level.